6 Let \( f \) be the function defined by \( f(x)=\frac{a x+b}{c x+d} \) and its representative curve. Calculate the real numbers \( a, b, c \) and \( d \) so that (H) passes through the points \( A(4 ; 1) \) and \( B(-2 ; 4) \) and admits the line of equation \( y=3 \) as asymptote.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find the values of \( a, b, c, \) and \( d \), we know that the function \( f(x) = \frac{ax + b}{cx + d} \) needs to satisfy the following conditions: 1. The function passes through the points \( A(4, 1) \) and \( B(-2, 4) \). 2. The horizontal asymptote is \( y = 3 \). From the asymptote condition, we know that as \( x \to \infty \), \( f(x) \approx \frac{a}{c} \). For this to equal 3, we have the equation: \[ \frac{a}{c} = 3 \quad \Rightarrow \quad a = 3c. \] Now we'll substitute this relationship into the equations derived from the points A and B. **Using Point A (4, 1):** \[ f(4) = \frac{3c(4) + b}{c(4) + d} = 1, \] which leads to: \[ 12c + b = 4c + d. \] Rearranging gives us: \[ 8c + b - d = 0 \quad \text{(1)}. \] **Using Point B (-2, 4):** \[ f(-2) = \frac{3c(-2) + b}{c(-2) + d} = 4, \] so we have: \[ -6c + b = -2c + d. \] Rearranging gives us: \[ -4c + b - d = 0 \quad \text{(2)}. \] Now we can solve the system of equations formed by (1) and (2): From (1): \[ b = d - 8c, \] Substituting into (2): \[ -4c + (d - 8c) - d = 0, \] which simplifies to: \[ -4c - 8c = 0 \quad \Rightarrow \quad -12c = 0. \] This implies \( c = 0 \), which isn’t viable since it would make \( f(x) \) undefined. Next, let's directly encode \( b \) and \( d \) in terms of \( c \) from the asymptote condition. From the above solutions, we can express both equations in \( d \): Using (1) and solving for \( d \): \[ d = 8c + b, \] and substituting \( d \) into (2): \[ -4c + b - (8c + b) = 0 \Rightarrow -4c - 8c = 0 \implies b = 12c. \] Now with \( b = 12c \): Substituting \( b = 12c \) back into the equation for \( d \): \[ d = 8c + 12c = 20c. \] So we have \( a = 3c, b = 12c, d = 20c \). Now we just need arbitrary values for \( c \) to find specific values. If we choose \( c = 1 \): - \( a = 3(1) = 3 \) - \( b = 12(1) = 12 \) - \( d = 20(1) = 20 \) Thus, our coefficients are: \[ a = 3, \quad b = 12, \quad c = 1, \quad d = 20. \] The final function is: \[ f(x) = \frac{3x + 12}{x + 20}. \]